Choices & consequences : what to do when a teenager uses alcohol/drugs : a step-by-step system that really works - Schaefer, Dick; Espeland, Pamela, 1951- (Minneapolis : Johnson Institute Books, 1987)
Written for parents, teachers, family doctors, mental health professionals, school guidance counsellors, social workers, juvenile justice workers, clergy, and anyone else who cares about teenagers, it describes a step-by-step process called intervention that you can use to stop a teenager's harmful involvement with chemicals
1. "You sat on the burner, baby, you sit on the blisters" and other basic principles of intervention -- Part I. Learning about teenage chemical dependence -- 2. Why teenagers use alcohol/drugs -- 3. The addiction process -- 4. The feeling disease -- 5. How chemical dependence in teenagers differs from chemical dependence in adults -- 6. From use to addiction: an overview of teenage involvement with alcohol/drugs -- 7. How to tell if a teenager is using and how bad it really is -- 8. The tasks of adolescence -- 9. The adolescent delusional system -- Part II. Intervening with teenagers in trouble with alcohol/drugs -- 10. Disengagement: preparing for intervention -- 11. The professional's role in disengagement -- 12. Confrontation: doing intervention -- 13. The professional's role in confrontation -- 14. Reintegration: following up intervention
Includes bibliographical references (pages 140-141) and index
Keywords: Teenagers -- Alcohol use -- United States; Alcoholism -- United States -- Prevention; Teenagers -- Drug use -- United States; Drug abuse -- United States -- Prevention; Teenagers -- United States -- Alcohol use; Alcoholism; Drug abuse; Drug addiction; Drug abuse -- United States -- Prevention; Alcoholism; Adolescent; Alcoholism -- prevention & control; Substance-Related Disorders; Substance-Related Disorders -- prevention & control; alcoholism; drug addiction; drug abuse; Youth -- Alcohol use; Paperback